Generała Kazimierza Sosnkowskiego sejmowy patron roku 2025 i jego obraz we współczesnych podręcznikach do nauczania historii w szkołach ponadpodstawowych (licea i technika) - Białokur, Marek; Biedka, Karolina; Gołębiowski, Dariusz (Studia Edukacyjne, 2025)
The aim of this article is to present the significance of Polish Parliament’s resolution proclaiming 2025 as the Year of General Kazimierz Sosnkowski and to examine the presence of this historical figure in upper secondary school history textbooks. The origins and course of the legislative process are discussed, with emphasis on the commemorative and educational roles such resolutions play within politics of memory. In the research section, several contemporary history textbooks used in Polish upper secondary schools are analyzed, focusing on the portrayal of Sosnkowski, the historical context, and the educational role as-signed to him. The findings reveal that the general is significantly underrepresented in current teaching materials, particularly relevant in light of his designation as patron of the year. The text emphasizes the need to use parliamentary commemorative resolutions as a stimulus for revising and enriching textbook narratives and for undertaking complementary educational initiatives.